Enhancing Wheat Flour Quality Through Introgression of High-Molecular-Weight Glutenin Subunits From Aegilops tauschii Accessions - Mohamed, Ikram Elsadig Suliman; Oe, Haruka; Kamal, Nasrein Mohamed; Mustafa, Hala Mohammed; Gorafi, Yasir Serag Alnor; Tahir, Izzat Sidahmed Ali; Tsujimoto, Hisashi; Tanaka, Hiroyuki (Frontiers in Sustainable Food Systems, 2022)
Narrow genetic diversity in the wheat gene pool restricts the improvement of wheat quality traits. Aegilops tauschii possesses valuable genetic diversity that can be used to improve not only biotic and abiotic stresses in arid regions but also wheat yield and quality. Our study, which used 392 multiple synthetic derivatives (MSD) panel developed with Ae. tauschii Coss. introgressions, had three main aims: to explore the genetic diversity of high-molecular-weight glutenin subunits (HMW-GS), to investigate the dough strength and the relationship between protein content and grain yield, and to identify lines with a good flour quality. A wide range of allelic diversity was observed at the Glu-D1 locus, reflecting the impact of the different introgressed portions of Ae. tauschii, and a wide variation was found in dough strength even between lines having the same composition of HMW-GS. We report a negative impact on dough strength of subunit 5t+10t from Ae. tauschii and a relatively positive impact of subunit 2t+12.1t. We identified four MSD lines with significantly enhanced flour quality. Regressing the grain yield of the MSD lines against protein content showed no correlation between the two traits and identified lines with comparable grain yield to the recurrent parent and higher protein content. The identified MSD lines could provide a valuable genetic resource for enhancing the end-use quality of flour without any loss in productivity.